Clinicopathological features and prognostic analysis of signet ring cell gastric carcinoma: a population-based study - Guo, Shuai; Shang, Mu-Yan; Dong, Zhe; Zhang, Jun; Wang, Yue; Zheng, Zhi-Chao; Zhao, Yan (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: The impact of signet ring cell carcinoma (SRC) on gastric cancer patients’ prognosis remains controversial. The aim of this study was to evaluate the clinicopathological characteristics and prognosis of SRC carcinoma and adenocarcinoma (AC) in patients with gastric cancer (GC). Methods: An electronic search of SRC and AC cases from 2004 to 2015 was conducted within the National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) database. According to histological type, AC patients were divided into two groups: well- and moderately differentiated (WMD) and, poorly differentiated adenocarcinoma (PD). Kaplan-Meier (KM) curves were used to compare 5-year overall survival (OS), Univariate, and multivariable analysis were performed by Cox regression model. Results: We identified 29,851 gastric cancer patients, among whom 16,482 were in the M0 group and 13,369 were in the M1 group. SRC patients had younger age distribution and were more seen in women. SRC was more likely to be found in advanced T and N stage, and with more distant metastasis. The most common metastatic site was bone-in SRC, while the most common site was the liver for WMD and PD. In the M0 group, multivariable analyses demonstrated that SRC had a similar survival rate with WMD and PD in stage I, and with the stage increasing, the overall survival of SRC was worse than that of WMD. Meanwhile, in the M1 group, SRC had an even worse prognosis than PD. Conclusions: SRC was significantly different from AC in its clinicopathologic characteristics. Although the prognosis of SRC was similar to AC in the early stage, it had a more inferior prognostic impact with the progression of the disease. Different therapeutic regimens and imaging evaluations should be applied according to the histological types of gastric cancer.